Science and judicial reasoning : the legitimacy of international environmental adjudication - Sulyok, Katalin, 1986- (Cambridge studies on environment, energy and natural resources governance, 2022)
"Science often entails connotations of 'objectivity', 'certainty', and the capability to discover the 'factual truth'. Judicial decisions, in turn, are routinely associated with resolving disputes in a 'final', 'neutral', and 'authoritative' way. Yet international environmental adjudication, where scientific and legal authority get entangled with each other, suggests that neither science nor law can fully live up to these idealized expectations. What happens if science and law yield competing narratives as to the factual basis of a dispute? Who could and should resolve their conflict and how, based on what benchmarks? Would the uncertain, probabilistic nature of scientific input diminish the authority of a legal judgment based upon it?"--